THE MAPPAJE TRADITION OF THE COMMUNITY OF PARENRENG VILLAGE, SEGERI DISTRICT, PANGKEP REGENCY - Abd. Rahim; M. Saleh Ridwan; Zulhas’ari Mustafa (Pascasarjana UIN Alauddin Makassar, 2022)
The type of research used in this study is descriptive qualitative research, regarding the Mappaje tradition in wedding parties in the Bugis-Makassar community, especially in Parenreng Village, Segeri District, Pangkep Regency by taking field data (Field Research). The data obtained in the form of descriptive data with the form of spoken or written words from informants and actors that can be considered. The Mappaje' tradition is contrary to Islamic law regarding the issue of faith where they believe when doing Mappaje' to obtain salvation and prevent evil while in Islamic values ​​and teachings it requires Muslims to only depend on Allah SWT and nothing can bring good or bad, even badness except by the power of Allah SWT.